New Research Trends for Textiles - Dufossé, Laurent (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
PART 1. Functional Textiles: Photochromic Textiles Based upon Aqueous Blends of Oxygen-Deficient WO3-x and TiO2 Nanocrystals. 50/60 Hz Power Grid Noise as a Skin Contact Measure of Textile ECG Electrodes. Characterizing Steam Penetration through Thermal Protective Fabric Materials. Stretchable Textile Yarn Based on UHF RFID Helical Tag. Fibers and Textiles for Personal Protective Equipment. Textile-Based Sound Sensors (TSS). High-Performance and Functional Fiber Materials. Geotextiles-A Versatile Tool for Environmental Sensitive Applications in Geotechnical Engineering. Review of Fiber- or Yarn-Based Wearable Resistive Strain Sensors. Wearable Actuators: An Overview. Bacterial Secondary Metabolites as Biopigments for Textile Dyeing. PART 2: Process and Modelling. Loop Order Analysis of Weft-Knitted Textiles. New Geometrical Modelling for 2D Fabric and 2.5D Interlock Composites. Meso-Macro Simulations of the Forming of 3D Non-Crimp Woven Fabrics. Continuous Yarn Electrospinning. A Review on Tough Soft Composites at Different Length Scales. Textile Branch and Main Breakthroughs of the Czech Republic in the Field of Textile Machinery. Recent Efforts in Modeling and Simulation of Textiles. PART 3: Control. A Comparison of Two Different Light Booths for Measuring Color Difference of Metameric Pairs. Effect of Textile Characteristics on the AR-Glass Fabric Efficiency. Dielectric Properties of Textile Materials. PART 4: Consumers and Behavior. Development of a Consumer-Based Quality Scale for Artisan Textiles. Organic Cotton Clothing Purchase Behavior. A Review on Textile Recycling Practices and Challenges.